Public Health and Sustainable Development: Assessing SDG3 across the Countries of the European Union - Elżbieta Sobczak; Dariusz Głuszczuk (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: To classify EU countries by their degree of implementation of Sustainable Development Goal 3 – good health and well-being; to identify the changes which have occurred in two years, 2016 and 2020.